Characterization and antimicrobial activities of two Streptomyces isolates from soil in the periphery of Universiti Putra Malaysia. - Mohamad Zin, Nurul Zarith; Tasrip, Nor Asmara; Mohd Desa, Mohd Nasir; Cheah, Yoke Kqueen; Zakaria, Zainul Amiruddin; Awang Hamat, Rukman; Shamsudin, Mariana Nor (Malaysian Society of Parasitology and Tropical Medicine, 2011)
This study was to assess the identification and antimicrobial activities of two actinomycete isolates. The two isolates designated as B8 and C2, were isolated from a patch of soil in the peripheral area of Universiti Putra Malaysia by streaking on starch casein agar after standard serial dilution procedures. Their antimicrobial activities were first evaluated against eight clinical laboratory strains namely Bacillus sp., Enterococcus sp., Escherichia coli, Klebsiella sp., Pseudomonas sp., Salmonella sp., Staphylococcus aureus, and Staphylococcus epidermidis by perpendicular streak method on Mueller Hinton and Tryptic Soy agar. In both media, a broad-spectrum antibacterial activity was observed for both isolates, with B8 against all the test bacteria and C2 against five of them (Bacillus sp., E. coli, Pseudomonas sp., S. aureus and S. epidermidis). Re-assessment against E. coli ATCC 25922 and S. aureus ATCC 25923 strains by similar method showed antibacterial activities by isolate B8 against both ATTC strains while C2 only against S. aureus ATCC 25923. Streptomyces griseus ATCC 10137 was included in the later experiment and showed antibacterial activity against both ATCC strains. Subsequently, the two isolates were identified by PCR/sequencing techniques and phylogenetic analysis to be Streptomyces species (>93% homology based on 16S rRNA and rpoB genes). Characterization on cultural characteristic and viable count at different temperatures (37ºC and 28ºC), on different microbiological media (AIA, ISP-2, MHA, NA, PDA and TSA), were performed. More morphological features were observed on ISP-2 for both isolates. A higher growth yield was also observed at 28ºC in all media but in comparing that between the two isolates, isolate B8 outnumbered C2 at all experimental conditions. The observed variation in cultural traits and growth yield indicate unique properties between the two antibiotic-producing isolates.